2022
DOI: 10.3389/fmed.2021.736320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperinsulinemia and Insulin Resistance on Endocrine, Metabolic, and Reproductive Outcomes in Non-PCOS Women Undergoing Assisted Reproduction: A Retrospective Cohort Study

Abstract: Objective: To evaluate the effect of hyperinsulinemia (HI) and insulin resistance (IR) on endocrine, metabolic, and reproductive outcomes in women without polycystic ovary syndrome (PCOS) undergoing assisted reproduction.Materials and Methods: The study included 1,104 non-PCOS women undergoing in vitro fertilization/intracytoplasmic sperm injection-fresh embryo transfer. HI was evaluated by serum fasting insulin (FIN), and IR was evaluated by homeostatic model assessment of insulin resistance index (HOMA-IR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…To our current knowledge, there is no report regarding the relationship between preconception IR and late miscarriage among non-dyslipidemic populations. Consistent with a previous study (31,32), our data shows an increased trend in serum levels of TG, LDL-C and a decreased trend in serum HDL-C level with the increased HOMA-IR group, even though the serum lipid levels were normal. After controlling for potential confounders, we confirmed that HOMA-IR is an independent risk factor for late miscarriage in either normolipidemic or non-PCOS women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To our current knowledge, there is no report regarding the relationship between preconception IR and late miscarriage among non-dyslipidemic populations. Consistent with a previous study (31,32), our data shows an increased trend in serum levels of TG, LDL-C and a decreased trend in serum HDL-C level with the increased HOMA-IR group, even though the serum lipid levels were normal. After controlling for potential confounders, we confirmed that HOMA-IR is an independent risk factor for late miscarriage in either normolipidemic or non-PCOS women.…”
Section: Discussionsupporting
confidence: 92%
“…Other reports, however, dispute these results (17,30,31). Wang et al failed to find significant differences in pregnancy outcomes, including pregnancy rate, clinical pregnancy loss rate, and cumulative live birth rate, between IR and non-IR group (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, although not included as variables in the current study, both HOMA and FFA are adipose tissue-related markers with potential impact on pregnancy and live birth outcome of IVF in overweight and obese women. In a recent retrospective cohort study of women undergoing IVF, HOMA was not associated with clinical pregnancy, live birth, and miscarriage 50 . Others report that insulin resistant women with PCOS have a lower implantation rate than non-insulin resistant women with PCOS, controlled for confounding factors including age, BMI, free androgen index and lipid profiles 51 .…”
Section: Discussionmentioning
confidence: 84%
“…With the development of clinical research on POCS, according to recommendations from the International Evidence-based Guideline for the Assessment and Management of Polycystic Ovary Syndrome from 2018 ( Teede et al, 2018 ), PCOS has been further distinguished into four phenotypes: phenotype A manifested as the excess of androgens, ovulatory dysfunction, and polycystic ovary on ultrasound; phenotype B manifested as the excess of androgens and ovulatory dysfunction; phenotype C manifested as the excess of androgens and polycystic ovary on ultrasound; and phenotype D manifested as ovulatory dysfunction and polycystic ovary on ultrasound. Although the guidelines mentioned above permit the diagnosis of PCOS, the clinical manifestations of PCOS are complex and reference multiple symptoms, such as ovarian enlargement ( Azziz et al, 2016 ; Escobar-Morreale, 2018 ), hyperandrogenism ( Rosenfield and Ehrmann, 2016 ; Ruth et al, 2020 ), insulin resistance ( Diamanti-Kandarakis and Dunaif, 2012 ; Azziz et al, 2016 ), hyperinsulinemia ( Housman and Reynolds, 2014 ; Muscogiuri et al, 2015 ; Cai et al, 2022 ), menstrual irregularity ( Jayasena and Franks, 2014 ; Pena et al, 2020 ), anovulation ( Dewailly et al, 2016 ; Carson and Kallen, 2021 ) or oligo-anovulation ( Hickey et al, 2012 ; Tay et al, 2020 ), infertility ( Carson and Kallen, 2021 ), and others. At the same time, PCOS significantly increases the risk of cardiovascular disease ( Okoth et al, 2020 ; O'Kelly et al, 2022 ), type 2 diabetes ( Diamanti-Kandarakis and Dunaif, 2012 ; Azziz et al, 2016 ; Zhu et al, 2021 ), obesity ( Lim et al, 2012 ; Lim et al, 2013 ; Sermondade et al, 2019 ), and metabolic disorders ( Rosenfield and Ehrmann, 2016 ; Escobar-Morreale, 2018 ).…”
Section: Introductionmentioning
confidence: 99%